From thankfulness to taking it for granted – a qualitative study of dental education during COVID - Goetz, Katja; Reimer, Ida; Wenz, Hans-Jürgen; Hertrampf, Katrin (Frontiers in Education, 2024)
IntroductionThe coronavirus (COVID-19) pandemic brought public life to a standstill. For universities, this meant the suspension or corresponding adjustment of practical and theoretical teaching. In Germany, the Kiel Dental Clinic received special permits to start face-to-face teaching under appropriate hygienic conditions. Therefore, the aim of this study, which was conducted using a longitudinal qualitative panel, was to interview students and teachers over a period of three semesters under pandemic conditions regarding the effects of the pandemic on dental teaching at a structural, individual and social aspect in order to determine which strategies can be acquired for future teaching design.MethodsQualitative methods based on interviews were used for data collection. The same dental students from different semesters (6th, 8th and 10th) and the same teaching staff responsible for the content and implementation of courses within the dental curriculum were interviewed in the summer semesters of 2020 and 2021. The data analysis was performed by qualitative content analysis.ResultsA total of 27 students and 15 teaching staff participated. Our study team received interesting results on the implications of the teaching and learning situation from the start of the emergency transition to remote teaching and then to practical courses in face-to-face situations with specific regulations. Teaching under pandemic conditions resulted in a very stressful situation for the students and teaching staff. The learning process for teaching has led to an improvement in digital literacy for both groups over the last two years.DiscussionThis qualitative longitudinal study describes the different factors that played a role during the course of the various “Corona” semesters. The development process, from thankfulness to taking it for granted, demonstrated that students’ expectation towards the implementation of the courses increased. Simultaneously, the results clearly show that the degree of stress and anxiety among students and teachers increased also. The necessary self-structuring of everyday student life under COVID conditions was not possible for everyone. It was also noted that teachers in particular were aware of this and that they developed a certain vigilance towards students.